Sharing out the land of the Northumbrians: exploring Scandinavian settlement in eastern Yorkshire through -bý place-names and township boundaries (part two) - Wrathmell, Stuart (Medieval Settlement Research, 2021)
The extent and character of Scandinavian settlement in the Danelaw have been debated for over half a century by place-name scholars, historians and archaeologists. This article, the second of three, explores some of the key issues through detailed studies of rural communities in eastern Yorkshire, focusing on place-names ending in -bȳ and the character of the township territories to which these names were applied. Building on the conclusions of the previous article in the series, it identifies different patterns of -bȳ township, and argues that these differences can be explained by the stage reached in the formation of rural communities at the point at which they were disrupted by Scandinavian settlement.